Florence's Statistical Method in Economics and Political Science - Dickinson, Z. Clark (Quarterly Journal of Economics, 1931)
Journal Article Florence's Statistical Method in Economics and Political Science Get access Z. Clark Dickinson Z. Clark Dickinson University of Michigan Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 45, Issue 2, February 1931, Pages 347–351, https://doi.org/10.2307/1885478 Published: 01 February 1931